Impact resistance of shear thickening fluid/Kevlar composite treated with shear-stiffening gel. (March 2018) - He, Qianyun; Cao, Saisai; Wang, Yunpeng; Xuan, Shouhu; Wang, Pengfei; Gong, Xinglong
Abstract: In this work, shear-stiffening gel (STG) was introduced into shear thickening fluid (STF)-impregnated-Kevlar® woven fabric (Kevlar/STF) to improve the impact resistance. The STF filled within the yarns of Kevlar and the STG covered the Kevlar/STF to form Kevlar/STF/STG composite. The STG in the Kevlar/STF/STG not only protected STF but also improved the impact resistance of the fabric because of its excellent shear-stiffening characteristics. A series of experiments including the yarn pull-out test, the split Hopkinson pressure bar impact test, rod penetration test, and knife cutting test were carried out to verify the enhancement effect. The improvement mechanism of the impact resistance for the Kevlar/STF/STG was studied. Under the similar anti-impact performance, the Kevlar/STF/STG possessed lower weight than the Kevlar and its strong impact resistance originated from the synergetic effect among the STF, STG and Kevlar. Therefore, the Kevlar/STF/STG exhibited broad potential in the soft body armor.